Impact of Extended Membrane Rupture on Neonatal Inflammatory Responses and Composite Neonatal Outcomes in Early-Preterm Neonates—A Prospective Study - Maura-Adelina Hincu; Liliana Gheorghe; Luminita Paduraru; Daniela-Cristina Dimitriu; Anamaria Harabor; Ingrid-Andrada Vasilache; Iustina Solomon-Condriuc; Alexandru Carauleanu; Ioana Sadiye Scripcariu; Dragos Nemescu (Diagnostics)
Background/Objectives: Prolonged prelabour rupture of membranes (PROMs), and the resulting inflammatory response, can contribute to the occurrence of adverse neonatal outcomes, especially for early-preterm neonates. This prospective study aimed to measure neonates’ inflammatory markers in the first 72 h of life based on ROM duration. The second aim was to examine the relationship between PROMs, serum inflammatory markers, and composite adverse neonatal outcomes after controlling for gestational age (GA). Methods: Data from 1026 patients were analyzed considering the following groups: group 1 (ROM < 18 h, n = 447 patients) and group 2 (ROM > 18 h, n = 579 patients). These groups were further segregated depending on the GA at the moment of membranes’ rupture into subgroup 1 (<33 weeks of gestation and 6 days, n = 168 patients) and subgroup 2 (at least 34 completed weeks of gestation, n = 858 patients). Multiple logistic regressions and interaction analyses adjusted for GA considering five composite adverse neonatal outcomes and predictors were employed. Results: PROMs and high c-reactive protein (CRP) values significantly increased the risk of composite outcome 1 occurrence by 14% (95%CI: 1.03–1.57, p < 0.001). PROMs and high CRP values increased the risk of composite outcome 5 by 14% (95%CI: 1.07–1.78, p < 0.001), PROM and leukocytosis by 11% (95%CI: 1.02–1.59, p = 0.001), and PROMs and high PCT values by 21% (95%CI: 1.04–2.10, p < 0.001). Conclusions: The combination of PROMs and high CRP values significantly increased the risk of all evaluated adverse composite outcomes in early-preterm neonates and should point to careful monitoring of these patients.